The effect of the Benson relaxation technique on sleep quality in women with breast cancer after mastectomy - Razieh Chabok; Arezoo Gholami; Neda Mahdavifar; Mostafa Rad (Golestan University of Medical Sciences, 2023)
Background: Sleep disorder is common in women with mastectomy. Previous studies have shown that relaxation technique improves sleep quality. However, the effects of these interventions on the sleep quality of breast cancer patients who underwent mastectomy surgery is still unclear. This study aimed to determine the effect of the Benson relaxation technique (BRT) on sleep quality in women with breast cancer after mastectomy. Methods: This randomized clinical trial study was performed on 72 eligible patients who were referred to the screening and chemotherapy center of Shahid Modares Hospital of Kashmar City from April to July 2021. The patients were selected through convenient sampling and randomly allocated to intervention (n = 36) and control (n = 36) groups. In the intervention group, in addition to the routine treatments, BRT was performed once in the morning and once in the evening for 2 months, each time for 20 minutes. The Pittsburgh Sleep Quality Index (PSQI) was used to evaluate the score of sleep quality at the beginning of the study and 2 months later. Data were analyzed using the paired t test and independent t test at 95% CI. Results: The mean score of sleep quality before the intervention in the intervention and control groups was 9.25 ± 2.50 and 8.47 ± 2.13, respectively. After the intervention, the mean score of sleep quality in the intervention and control groups was 6.63 ± 1.92 and 8.41 ± 2.15, respectively, and the difference was significant between the 2 groups (P = 0.001) Conclusion: The Benson relaxation technique improves sleep quality in women with breast cancer after mastectomy. Therefore, it can be considered an adjunct therapy to improve the sleep quality in these people.